Oral Carriage of Streptococcus mutans Harboring the cnm Gene Relates to an Increased Incidence of Cerebral Microbleeds. Issue 12 (December 2020) - Hosoki, Satoshi; Saito, Satoshi; Tonomura, Shuichi; Ishiyama, Hiroyuki; Yoshimoto, Takeshi; Ikeda, Shuhei; Ikenouchi, Hajime; Yamamoto, Yumi; Hattori, Yorito; Miwa, Kaori; Friedland, Robert P.; Carare, Roxana O.; et al.
Abstract : Background and Purpose: Cerebral microbleeds (CMB) are associated with stroke and cognitive impairment. We previously reported a high prevalence of CMB in people with Streptococcus mutans expressing Cnm, a collagen-binding protein in the oral cavity. S. mutans is a major pathogen responsible for dental caries. Repeated challenge with S. mutans harboring the cnm gene encoding Cnm induced cerebral bleeding in stroke-prone spontaneously hypertensive rats. The purpose of this longitudinal study is to examine the relationship of cnm -positive S. mutans to the development of CMB. Methods: We retrospectively investigated patients with stroke receiving oral microbiological examination and head 3T magnetic resonance imaging evaluations twice in the period 2014 to 2019, allowing >180-day interval. Patients with cnm -positive S. mutans were compared with those without. Quasi-Poisson regression models were used to explore associations between cnm -positive S. mutans and the increase in number of CMB between the 2 magnetic resonance imaging scans. Results: A total of 111 patients were identified; 21 (19%) with cnm -positive S. mutans and 90 (81%) without. Clinical history, including blood pressure and the use of antithrombotic agents, were comparable between the 2 groups. New CMB were more commonly observed in patients with cnm -positive S. mutans (52% versus 23%; P =0.008). The incidence of CMB was significantly higher in the group with cnm -positive S. mutans, especially in deep areas, (incidence rate ratios [95% CI], 5.1 [1.9–13.6] for CMB in any brain region; 15.0 [5.4–42.0] for deep CMB), which persisted after adjusting for age, sex, hypertension, and renal impairment (4.7 [1.8–11.9] for CMB in any brain region; 13.9 [4.3–44.5] for deep CMB). Conclusions: This study demonstrates that cnm -positive S. mutans is associated with an increased incidence of CMB. Treatment for cnm -positive S. mutans infection may be a novel microbiota-based therapeutic approach for stroke and cognitive impairment. Abstract : Supplemental Digital Content is available in the text.